(untitled) (Fiep Bulletin - online, 2013)
This study had as objective to evaluate the Quality of Life at Work in the work environment, demonstrating the impact of the factors that influence the organizational environment, as well as the welfare of the population and how this is reflected in the daily; also had as objective to determine the internal consistency of the questionnaire QVS-80, in two applications. It has participated of the study 30 individuals of both sexes, employees of a company in the city of Ponta Grossa PR. To measure the quality of life using the questionnaire Quality of Life and Health 80 (QVS-80), with two applications in a range of fifteen days between them. To analyze the reliability of the instrument used, It is calculated the internal consistency through of Cronbach’s alpha. The questionnaire showed an excellent reliability in both applications, with Cronbach’s alpha 0,808 and 0,859 respectively. On the results about Quality of Life at Work it can be observed that the Dominion Physical activity showed unsatisfactory results, since physical activity has an influence on the health and welfare of the individual, consequently in their occupational environment, because the physical activity plays an important role in QOF. Whereas much of the population does not perform regular physical activity, what influences in all other areas of their lives, including the work environment. Programs to encourage the practice of regular physical activity and targeted are increasingly needed within companies, thus wins the official, the company wins and earns the country.